Epistemology of the Interpretation of Tajul Muslimin Min al-Kalam al-Rabb al-‘Alamiin by Misbah Mustafa - Nurdin, Aldi; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2025)
This article attempts to examine the epistemological dimension of a local interpretation by a Nusantara scholar, namely Tafsir Tajul Muslimin Min al-Kalam al-Rabb al-'Alamiin by Misbah Mustafa. Misbah Mustafa's interpretation in his work is strongly influenced by the scientific background and socio-political dynamics of Javanese Islamic society at that time. This study employs a historical-philosophical approach, utilising a qualitative research method that involves descriptive analysis. The data used are derived from literature studies, particularly those related to the interpretation of Tajul Muslimin and other relevant literature that support this research. The results of this study are that Misbah Mustafa's interpretation in his work is influenced by at least two factors: internal factors, such as the scientific background of traditional Islamic boarding schools that tend towards socio-community studies, and external factors, namely the cultural and political situation at the time of writing. Regarding the epistemological structure of Tajul Muslimin's interpretation, in terms of the sources of interpretation used, it is classified as tafsir bi al-ra'yi al-Mahmud or also called burhani epistemology. Meanwhile, the interpretive method used by Misbah is generally classified as at-tahlili (analysis), and specifically, the author identified at least 10 distinct steps employed by Misbah in his interpretation. Then, regarding the validity of Misbah Mustafa's interpretation in his interpretation, the author concluded that his interpretation contains elements of three theories of truth in philosophy: coherence, correspondence, and pragmatism.